The Influence of Instagram Usage on Narcissistic Behavior among Adolescents: A Quantitative Study in an Indonesian Secondary School - Pratiwi, Rani Diah; Aunurrahman; Halida; Karolina, Venny; Affandi (Universitas Islam Negeri Raden Intan Lampung, 2025)
The rapid growth of social media, particularly Instagram, has transformed patterns of adolescent social interaction and self-presentation, raising concerns about its psychological implications, including the emergence of narcissistic behavior. This study aims to examine the effect of Instagram usage on narcissistic behavior among tenth-grade students at SMA Negeri 1 Sintang. Employing a quantitative, descriptive-analytic design, data were collected from 251 students using validated self-report questionnaires that measured Instagram usage intensity and narcissistic behavior. Descriptive statistics and simple linear regression analysis were used to analyze the data. The results indicate that Instagram usage among students is relatively high and that narcissistic behavior is prevalent at a high level. Regression analysis reveals that Instagram usage has a significant positive effect on narcissistic behavior, with a strong correlation and a substantial proportion of variance explained. These findings suggest that increased engagement with Instagram’s visual and feedback-driven features contributes meaningfully to the development of narcissistic tendencies during adolescence. The study extends the existing literature by providing empirical evidence from a non-metropolitan secondary school context in Indonesia, which has been underrepresented in prior research. The findings imply that educators, school counselors, and policymakers should prioritize digital literacy education and psychosocial interventions to promote responsible social media use and mitigate potential negative impacts on adolescent personality development.